Decision Support System for New Employee Placement on An Office Department by Using Saw Fuzzy (case Study: CV.Kencana Abadi) - Indah Sri Rahayu; Syariful Alim; Rifki Fahrial Zainal (Fakultas Teknik Universitas Bhayangkara, 2017)
CV. KENCANA ABADI is a company engage for sale Castrol Oil in which there are several departments of HRD,accounting, finance & tax (tax), lubricant general manager and IT. During this time to determine the placement ofnew employees to the appropriate department still using the manual system. So needed a system needs that can be adecision support system for placement of new employees to appropriate departments that help the HRD and GA inorder to decide the right position placement for new employees. The model used in this decision support system isFuzzy Multiple Attribute Decision Making (FMADM). This SAW method is chosen because it determines the weightvalue for each attribute, followed by a ranking process that will select the best alternative from a number ofalternatives. Based on the results of testing HRD departments are eligible received Fajar Ferdhina, the test resultsof the Finance department, Accounting, Tax Budi Setyawan eligible, the results of testing IT departments eligibleGatot Nugroho, and the results of testing department Lubrican General Manager eligible Imelda Oktavia F.